2018
DOI: 10.5694/mja17.00951
|View full text |Cite
|
Sign up to set email alerts
|

The management of epilepsy in children and adults

Abstract: The International League Against Epilepsy has recently published a new classification of epileptic seizures and epilepsies to reflect the major scientific advances in our understanding of the epilepsies since the last formal classification 28 years ago. The classification emphasises the importance of aetiology, which allows the optimisation of management. Antiepileptic drugs (AEDs) are the main approach to epilepsy treatment and achieve seizure freedom in about two-thirds of patients. More than 15 second gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
0
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 49 publications
3
146
0
22
Order By: Relevance
“…Since 1978, numerous new AEDs with similar efficacy to the old AEDs but improved side effect profiles and safety 6,7 have been marketed. Most of these are listed on the PBS but with varying degrees of prescribing restrictions.…”
Section: Perspectivesmentioning
confidence: 99%
“…Since 1978, numerous new AEDs with similar efficacy to the old AEDs but improved side effect profiles and safety 6,7 have been marketed. Most of these are listed on the PBS but with varying degrees of prescribing restrictions.…”
Section: Perspectivesmentioning
confidence: 99%
“…In adults, benzodiazepines [specifically (IM) Midazolam, Lorazepam (IV) or Diazepam (IV)] are recommended as the initial therapy of choice, given its demonstrated efficacy, safety and tolerability (level of evidence A, class I) (Fiest et al, 2017, Glauser et al, 2016, Perucca, Scheffer & Kiley, 2018.…”
Section: Status Epilepticusmentioning
confidence: 99%
“…It is estimated that the risk of recurrence of a person who had two crises not provoked again to have epileptic seizures is around 60-90% (Table 5) (Johnson, 2019). On the other hand, epilepsy is considered to be resolved in those individuals who had epilepsy related to a specific age group and who exceeded that age or those who had the last crisis for more than 10 years and have been at least five years without Use antiepileptic medications (Martinez-Juarez et al, 2016, Perucca, Scheffer & Kiley, 2018.…”
Section: Prognosismentioning
confidence: 99%
“…The classic ketogenic diet is based on a 4:1 of fat to carbohydrate ratio [41]. The ketogenic diet has been proven to be beneficial to patients with drug-resistant epilepsy [42]. One study showed that 38% children in the study who had been placed on ketogenic diet for three months experienced a reduction in seizures by over 50% compared to 6% in the control group [43].…”
Section: Ketogenic Diet Causes Selenium Deficiency and Cardiomyopathymentioning
confidence: 99%